Users’ Perception on Knowledge Transfer via Mobile Money Services - Nurdiana Azizan; Noraizah Abu Bakar; Asma Abdul Rahman (Universiti Sains Islam Malaysia, 2024)
Mobile money is an electronic wallet service that allows users to store, send, and receive money. Safe and easy electronic payments make mobile money a popular alternative to bank accounts. Despite the convenient services offered to users, the adoption of mobile money is still low. Due to that, the objective of this study is to assess the perceptions of users on mobile money services as a convenient payment alternative. This study adapted the intra-organizational knowledge transfer (KT) model to understand how users perceive mobile money services. This model has been chosen because it is well accepted and recognized among the researchers. Szulanski's intra-organizational KT model consists of four stages, namely initiation, implementation, ramp-up, and integration. This study adopted interpretive structural modeling (ISM) as the methodology. ISM is a well-established methodology for identifying relationships among specific items, which define a problem or an issue. This approach has been increasingly used by various researchers to represent the interrelationships among various elements related to the issue. The data were collected using the survey. The surveys were randomly distributed via e-mail to users in Malaysia. 481 responses answered the survey. On average 69% of the respondents know about mobile money and 31% of the respondents do not know about it. Having said that, 77% of the respondents have heard of mobile money services whereby only 23% have not heard about it. These results show that around 8% of the respondents heard of mobile money services but they do not find out what it means.